Reaction Systems: a Formal Framework for Processes Based on Biochemical Interactions - Ehrenfeucht, Andrzej; Rozenberg, Grzegorz (Electronic Communications of the EASST, 2010)
This paper presents a formal framework for investigating processes drivenby interactions between biochemical reactions in living cells. These interactions are based on the mechanisms of facilitation and inhibition, which underlie the definition of reaction systems - the central construct of our framework. We discuss in this paper the basic setup for reaction systems, and its motivation. We also present an important extension of reaction systems as well as some research topics and results.